The Identity of the Main Character in Nathaniel Hawthorne's Dr. Heidegger's Experiment: A Linguistic Analysis (Universitas Islam Negeri Sunan Ampel Surabaya, 2018)
This study analyzes the language used in the construction of the personal identity of Dr. Heidegger through the labels attached to him, both given by self and by others, and his stancetaking. The researcher applies Discourse Analysis to analyze the main character’s utterances. In addition, the researcher also uses Indexicality Principle by Bucholtz and Hall (2005) as a mechanism to analyze identity. Qualitative content analysis is used to analyze thoroughly and interpret text data to draw inference towards the utterances on the short story. The result of the study show that Dr. Heidegger is labeled mostly with negative words by others, however, he responded to combat these labels by using re-appropriation or by revaluing the existing labels. Moreover, the stances taken by Dr. Heidegger are found to position himself among others. Together with the labels given by self and others, and his interlocutor(s) in his talk-in-interactions the findings reveal that the he is a strange old man, who is very curious and knowledgeable. Lastly, the conclusion can also be drawn that language and discourse are central to the construction of identities that are not always determined by a person himself, but also bound up with how others perceive him.